Path Loss Analysis of RFID Channles Measurement in Library with Metal Bookshelves - Supramongkonset, Jatuporn; Promwong, Sathaporn (My University, 2023)
The radio frequency identification (RFID) library management system has gained popularity in libraries due to its convenience and improved efficiency. Accurate channel modeling is crucial for predicting system performance and received power. This paper focuses on modeling the channel characteristics of metal bookshelves in RFID library management systems operating at a frequency of 2.45 GHz. We employ microstrip patch antennas as both transmitter (Tx) and receiver (Rx) antennas, considering both vertical-vertical (V-V) and horizontal-horizontal (H-H) polarizations. Linear regression analysis models the path loss characteristic, allowing us to establish a mathematical relationship that accurately represents the path loss between the antennas. Furthermore, statistical models based on cumulative distribution function (CDF) are employed to characterize multipath fading, providing insights into the distribution of signal variations caused by multipath propagation. The experimental results indicate that metal bookshelves with V-V and H-H polarizations are suitable for the performance of RFID library management systems. The path loss models generated through linear regression analysis enable accurate prediction of received power, while the statistical models based on CDF contribute to a comprehensive understanding of multipath fading and its impact on system performance. This study provides valuable insights for librarians and system designers seeking to implement efficient and reliable RFID technology in library management systems. By examining and modeling the channel characteristics of metal bookshelves, our findings support the optimal use of V-V and H-H polarizations, ensuring the effective operation of RFID systems in library environments.
Keywords: library management system; metal bookshelves; path loss analysis; RFID; RFID management